A Comparative Study of English CV Writing Skills across Different Concentration at LP3I Polytechnic Padang - Aminah, Aminah (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
LP3I Polytechnic is known for its commitment to guarantee internship and employment opportunities for its students which the process starting in the fifth semester. To address this, ESP courses are offered across concentrations which consist of Computerized Business Management (CBM), Informatics Computer (IC) and Accounting Information System (AIS) to enhance their readiness for employment. One material that this course offered was writing CV. However, differences in English CV writing skills among concentrations indicate an emerging issue since this document is important in applying a job or internship. This study aims to compares these differences to inform improvements in ESP curriculum and pedagogy. This study was done by using qualitative comparative as research method. The data were collected through interview and document analysis. The findings show that accounting students have the best CVs among the concentrations. AIS students demonstrated stronger structure, language use, and design while CBM students have difficulties in CV grammar and organization and IC students are poorly organized CVs with numerous grammatical errors and insufficient reflection of their professional skills. Therefore, this study suggests workshops and giving personalized feedback to be given in order to improve students writing CV skill.